Developing case studies for implementing COST TU1406 quality control plan procedure for typical highway bridges - Kedar, Amir (2019)
An extensive work was done by COST TU1406 working groups (WG) 1,2 and 3 for preparing a guidance document for Quality Control Plan (QCP) of road bridges. WG 1, 2 and 3 reports named 'Performance Indicators for Roadway Bridges', 'Performance Goals for Roadway Bridges' and 'Establishment of a quality control plan' are already published. Based on these documents and the work done to-date, a new procedure for implementing the developed guidelines for the preparation of QCP for roadway bridges was developed by WG4 members in order to unify the method used and to validate the outcomes of the developed QCP. At the first stage, a set of common highway bridge prototypes were identified including girder, frame, arch and truss bridges. A database was created where each participating country has identified local bridges for developing of the case studies. Nine out of sixty bridges where selected for the first stage of preparing an example of QCP and the case study reports were compared with an objective to validate the outcomes. A guideline document was prepared with unified instruction on how to develop the national case study per country. The typical case study includes few stages which are defined based on the work done by WG1, 2 and 3. The stages includes data collection, element identification and grouping, defining vulnerable zones, damage processes and failure modes, selecting and evaluating performance indicators (PIs) and calculating key performance indicators (KPIs), establishing demands, creating QCP scenarios and comparing them by spider diagrams. First outcomes of the prototypes case study reports are now being updated to reflect the final version of WG3 report and together with the guidelines document will be distributed among participating countries to enable the benchmarking process for the full set of bridges representing Europe common highway bridge topologies.